Comparative Effects of Nitrogen Fertigation and Granular Fertilizer Application on Growth and Availability of Soil Nitrogen during Establishment of Highbush Blueberry - Bryla, David; Machado, Rui A. (Frontiers in Plant Science, 2011)
A 2-year study was done to compare the effects of nitrogen (N) fertigation and granular fertilizer application on growth and availability of soil N during establishment of highbush blueberry (Vaccinium corymbosum L. ‘Bluecrop’). Treatments included four methods of N application (weekly fertigation, split fertigation, and two non-fertigated controls) and four levels of N fertilizer (0, 50, 100, and 150 kg•ha-1 N). Fertigation treatments were irrigated by drip and injected with a liquid urea solution; weekly fertigation was applied once a week from leaf emergence to 60 d prior to the end of the season while split fertigation was applied as a triple split from April to June. Non-fertigated controls were fertilized with granular ammonium sulfate, also applied as a triple split, and irrigated by drip or microsprays. Weekly fertigation produced the smallest plants among treatments at 50 kg•ha-1 N in year 1 but the highest canopy cover at 150 kg•ha-1 N in both years 1 and 2. The other application methods required less N to maximize growth but were less responsive than weekly fertigation to additional N fertilizer applications. In fact, 44-50% of the plants died when granular fertilizer was applied at 150 kg•ha-1 N. By comparison, none of the plants died with weekly fertigation. Plant death with granular fertilizer was associated with high ammonium ion concentrations (up to 650 mg•L-1) and electrical conductivity (>3 dS•m-1) in the soil solution. Early results indicate that fertigation may be less efficient (i.e., less plant growth per unit of N applied) at lower N rates than granular fertilizer application but is also safer (i.e., less plant death) and promotes more growth when high amounts of fertilizer is applied.